2008
DOI: 10.1007/s10067-008-0960-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor may contribute to vasculopathy in systemic sclerosis

Abstract: Increasing evidence supports the concept of macrophage migration inhibitory factor (MIF) as a central proinflammatory cytokine in autoimmune diseases. To further evaluate its role in systemic sclerosis (SSc), serum levels of MIF were determined by enzyme-linked immunoassay, and correlations to clinical manifestations were analyzed in 43 patients. MIF levels were significantly increased in patients (median, 18.8; range, <0.015-189 ng/ml) in comparison to healthy controls (n=43, 8.0, <0.015-36.5 ng/ml; P<0.0005)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…Here, we examined concentrations of serum MIF and DDT in SSc and HC, in order to determine their clinical associations in SSc. In line with previous studies,9, 15 we found a significant increase in serum MIF concentrations in SSc patients compared to HC. However, there was no significant difference in serum DDT between SSc and HC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here, we examined concentrations of serum MIF and DDT in SSc and HC, in order to determine their clinical associations in SSc. In line with previous studies,9, 15 we found a significant increase in serum MIF concentrations in SSc patients compared to HC. However, there was no significant difference in serum DDT between SSc and HC.…”
Section: Discussionsupporting
confidence: 93%
“…However, whether this is the case in our data is not established and we found no significant correlation between serum MIF concentrations and mRSS in patients with diffuse SSc. The absence of differences in serum MIF according to other clinical parameters in SSc is in line with one previous study,14 but conflicts with other studies which have reported higher serum MIF in patients with diffuse SSc, PAH or digital ulcers 9, 10. The small size of these vascular phenotypic subsets in our study may explain these discrepancies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, elevated protein levels of this gene have been detected in the sera of dcSSc patients affected by PAH [13,21]. Moreover, Le Hiress et al showed through in vitro studies that MIF receptor (CD74) is overexpressed in individuals with idiopathic PAH [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased MIF protein levels have been reported in patients with idiopathic pulmonary fibrosis, pulmonary hypertension, and in individuals affected by SSc-associated PAH [11][12][13].…”
Section: Introductionmentioning
confidence: 99%